Peptidylarginine deiminase 4 deficiency in bone marrow cells prevents plaque progression without decreasing atherogenic inflammation in apolipoprotein E-knockout mice - Paunel-Görgülü, Adnana; Conforti, Andreas; Mierau, Natalia; Zierden, Mario; Xiong, Xiaolin; Wahlers, Thorsten (Frontiers in Cardiovascular Medicine, 2022)
Introduction Despite multiple studies in the past, the role of peptidylarginine deiminase 4 (PAD4) in atherosclerosis is currently insufficiently understood. In this regard, PAD4 deletion or inhibition of enzymatic activity was previously reported to ameliorate disease progression and inflammation. Besides, strong influence of neutrophil extracellular traps (NETs) on atherosclerosis burden has been proposed. Here, we studied the role of PAD4 for atherogenesis and plaque progression in a mouse model of atherosclerosis. Methods and results Lethally irradiated ApoE–/– mice were reconstituted with ApoE–/–/Pad4–/– bone marrow cells and fed a high-fat diet (HFD) for 4 and 10 weeks, respectively. PAD4 deficiency did not prevent the development of atherosclerotic lesions after 4 weeks of HFD. However, after 10 weeks of HFD, mice with bone marrow cells-restricted PAD4 deficiency displayed significantly reduced lesion size, impaired lipid incorporation, decreased necrotic core area and less collagen when compared to ApoE–/– bone marrow-transplanted mice as demonstrated by histological staining. Moreover, flow cytometric analysis and quantitative real-time PCR revealed different macrophage subsets in atherosclerotic lesions and higher inflammatory response in these mice, as reflected by increased content of M1-like macrophages and upregulated aortic expression of the pro-inflammatory genes CCL2 and iNOS. Notably, diminished oxLDL uptake by in vitro-polarized M1-like macrophages was evidenced when compared to M2-like cells. Conclusion These results suggest that pharmacological inhibition of PAD4 may impede lipid accumulation and lesion progression despite no beneficial effects on vascular inflammation.